1998
DOI: 10.1159/000014558
|View full text |Cite
|
Sign up to set email alerts
|

Photomodulation of the Melanocyte Cell Cycle by Indoleamines

Abstract: Melanocytes are photoresponsive cells which respond to varying doses of UV exposure in the G2 phase of the cell cycle by prominent dendricity. This photoresponse is related to indoleamine light sensitivity. The present study highlights the role of indoleamines in the photomodulation of the melanocyte cell cycle. The study was conducted on 40 whole-skin organ cultures taken from the marginal zone of vitiligo. Twenty organ cultures were subjected to G2-phase arrest, while 20 were incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
1
12
0
2
Order By: Relevance
“…It was further discovered that melatonin is important for mitotic activity in most lower organisms [2]. From studies in this laboratory, it has been observed that melatonin modulates the melanocyte cell cycle [3], and that indoleamines are expressed by and control melanocytes during the photoresponse [4][5][6]. Several workers have identified indoleamine activity in the skin [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It was further discovered that melatonin is important for mitotic activity in most lower organisms [2]. From studies in this laboratory, it has been observed that melatonin modulates the melanocyte cell cycle [3], and that indoleamines are expressed by and control melanocytes during the photoresponse [4][5][6]. Several workers have identified indoleamine activity in the skin [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have identified the presence of biogenic amines in melanocytes. These include catechol amines as well as indole amines [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Since this activity is cyclical with light and dark phases, both SER & MLT are expressed in these layers. In turn, the indoleamines modulate the melanocyte cell cycle in response to UV exposure [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of serotonin to melatonin is inhibited on exposure to a pulse of UV indicating the presence of the light sensitive enzymes NAT/HIOMT. 5 The epidermal melanocytes metabolise tryptamine 29 to produce indoleamines on UV exposure in whole skin organ cultures. In the TVC, indoleamines are positive in L2/L3 associated with mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the indoleamines modulate the melanocyte cell cycle in response to UV exposure. [4][5][6] Tyrosine is metabolised by several cell types which include catecholaminergic neurones in the brain and spinal cord, 31 sympathetic ganglia, adrenal medulla, and melanocytes which are neuroectodermal in origin. The metabolic pathway is through conversion of tyrosine to dopa, by catecholoxidase, a triphasic enzyme which catalyses both wings of dopa metabolism.…”
Section: Discussionmentioning
confidence: 99%